2017
DOI: 10.3389/fpsyg.2017.00490
|View full text |Cite
|
Sign up to set email alerts
|

Group Rumination: Social Interactions Around Music in People with Depression

Abstract: One of the most important roles that music serves in human society is the promotion of social relationships and group cohesion. In general, emotional experiences tend to be amplified in group settings through processes of social feedback. However, previous research has established that listening to sad music can intensify negative emotions in people with tendencies to rumination and depression. This study therefore investigated the phenomenon of ruminating with music, and the question of whether listening to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 41 publications
6
39
0
2
Order By: Relevance
“…Participants were recruited from among people who had taken part in an online survey and had indicated their interest in being involved in further research (Garrido et al, 2017). Initially, 615 people participated in the survey and were asked to complete the Depression and Anxiety Stress Scale (DASS; Henry and Crawford, 2005) and the Rumination-Reflection Questionnaire (RRQ; Trapnell, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…Participants were recruited from among people who had taken part in an online survey and had indicated their interest in being involved in further research (Garrido et al, 2017). Initially, 615 people participated in the survey and were asked to complete the Depression and Anxiety Stress Scale (DASS; Henry and Crawford, 2005) and the Rumination-Reflection Questionnaire (RRQ; Trapnell, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…Some indirect evidence supports the assumption that depressed individuals engage with sad stimuli for self-verifying reasons. For instance, individuals with depression were shown to use sad music to engage in rumination (i.e., to intensify negative affect and to focus on negative thoughts and memories) (Garrido et al, 2017). Likewise, individuals with tendencies to depression expected that listening to sad music will benefit them in some way, for instance because it makes them think about past events in their life (Garrido and Schubert, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In sum, studies on the pursuit of sadness with a special focus given to clinical depression have revealed somewhat contradictory findings. Whereas one study (Yoon et al, 2019) suggests that listening to sad music in depressed individuals is related to hedonic benefits (i.e., calming effects), some indirect evidence (e.g., Wilhelm et al, 2013;Garrido et al, 2017) suggests that the deliberate engagement with sad music is related to instrumental benefits (i.e., a verifying self-perception).…”
Section: Introductionmentioning
confidence: 99%
“…This study builds on a series of research that highlights how flourishing young people typically use music to promote positive states of being, but those with mental health problems are more likely to use music in ways that intensify anger or sadness (Garrido, Eerola, & McFerran, 2017; McFerran, Garrido, O’Grady, Grocke, & Sawyer, 2014). A critical review of the literature showed that researchers of this topic tend to be either blindly positive or determinedly negative in their investigation into how music works with young people, leading to confirmation bias (McFerran, Garrido, & Saarikallio, 2013).…”
mentioning
confidence: 99%